Peningkatan Pemahaman Sejarah melalui Model dan Media Pembelajaran Interaktif bagi Siswa SMK Muhammadiyah Ambon - Acim, Acim; Far-Far, Gazali; Harnisa, Susi; Maisuri, Tama; Kapitanhitu, Rehana; Matitaputty, Jani Koce (Universitas Pattimura, 2025)
Students of SMK Muhammadiyah Ambon face challenges in understanding historical material due to the dominance of lecture-based methods and the lack of interactive and contextual learning media. This condition leads to low learning motivation and minimal student engagement in the learning process. This community service activity aims to enhance students' understanding and motivation in learning history through the development of interactive learning media based on Android applications and Augmented Reality (AR). The method used is Participatory Action Research (PAR), with a collaborative and participatory approach involving teachers and students throughout the process. The activity stages include planning, teacher training, implementation of the media in classroom learning, and evaluation with follow-up. The results showed an increase in students' historical understanding scores from 55.3% to 78.4%, and an increase in motivation from a score of 3.1 to 4.2 (on a 5-point scale). The